2018
DOI: 10.1111/jvh.12945
|View full text |Cite
|
Sign up to set email alerts
|

Durability of virologic response, risk of de novo hepatocellular carcinoma, liver function and stiffness 2 years after treatment with ombitasvir/paritaprevir/ritonavir±dasabuvir±ribavirin in the AMBER, real‐world experience study

Abstract: We followed for 2 years patients treated with direct-acting agents (DAA) to assess long-term durability of virologic response, improvement of liver function, reduction in liver stiffness (LS) and risk of hepatocellular carcinoma (HCC). The study included patients from 16 hepatologic centres involved in the AMBER, investigator-initiated study on treatment of chronic hepatitis C patients within a programme preceding EU registration of ombitasvir/paritaprevir/ritonavir±dasabuvir±ribavirin. A total of 204 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
3
13
1
Order By: Relevance
“…In the study, they observed the evidently dropped aminotransferases (P < 0.0001), a progressive increase in serum albumin (P = 0.010), and a decrease in serum bilirubin (P = 0.011) as well as in gamma globulin (P = 0.0003) between baseline level and that after treatment [14]. A similar change was observed in other studies related to DAA and liver function repair [15,16], which confirms this tendency.…”
Section: Liver Function Repairsupporting
confidence: 83%
See 1 more Smart Citation
“…In the study, they observed the evidently dropped aminotransferases (P < 0.0001), a progressive increase in serum albumin (P = 0.010), and a decrease in serum bilirubin (P = 0.011) as well as in gamma globulin (P = 0.0003) between baseline level and that after treatment [14]. A similar change was observed in other studies related to DAA and liver function repair [15,16], which confirms this tendency.…”
Section: Liver Function Repairsupporting
confidence: 83%
“…Interestingly, with respect to patients who were diagnosed as liver fibrosis and cirrhosis, R. Flisiak et al found that their liver function improvement after DAA treatment was often better than that of non-cirrhotic patients [15]. The success of DAA treatment can reduce the liver stiffness value, which means the regression of fibrosis, the down-regulation of inflammatory activity and the improvement of blood circulation and the regression of hepatic steatosis [20].…”
Section: Liver Function Repairmentioning
confidence: 99%
“…Recently, DAAs were developed for CHC treatment that showed good efficacy, high SVR rates, and improved patient outcomes 35–37 . However, there is controversy regarding HCC development, as several studies reported a persistent risk of HCC after DAA treatment in CHC patients 38–40 . Regarding cumulative incidence of HCC, 1‐year cumulative incidence was estimated to be 3.7% in this meta‐analysis, similar or even slightly higher than pretreatment 1‐year cumulative incidence (2.4%) from Masuzaki et al 34 .…”
Section: Discussionmentioning
confidence: 53%
“…As demonstrated previously, treatment of patients with advanced liver disease is sometimes introduced too late to reverse development of hepatocellular carcinoma. 32 In 2015-2016, the majority of patients were treatment-experienced, whereas in 2018, previous therapy was reported only in 15%. In all 3 time intervals, a large majority (71%-81%) of retreated patients failed dual therapy with pegylated interferon plus ribavirin.…”
Section: Resultsmentioning
confidence: 99%